Arrested development-A comparative analysis of multilayer corona textures in high-grade metamorphic rocks - Ogilvie, P.; Gibson, R.L. (European Geosciences Union (EGU), 2017)
Coronas, including symplectites, provide vital clues to the presence of arrested reaction and preservation of partial equilibrium in metamorphic and igneous rocks. Compositional zonation across such coronas is common, indicating the persistence of chemical potential gradients and incomplete equilibration. Major controls on corona mineralogy include prevailing pressure (P), temperature (T ) and water activity (aH2O) during formation, reaction duration (t ) single-stage or sequential corona layer growth; reactant bulk compositions (X) and the extent of metasomatic exchange with the surrounding rock; relative diffusion rates for major components; and/or contemporaneous deformation and strain. High-variance local equilibria in a corona and disequilibrium across the corona as a whole preclude the application of conventional thermobarometry when determining P-T conditions of corona formation, and zonation in phase composition across a corona should not be interpreted as a record of discrete P-T conditions during successive layer growth along the P-T path. Rather, the local equilibria between mineral pairs in corona layers more likely reflect compositional partitioning of the corona domain during steadystate growth at constant P and T . Corona formation in pelitic and mafic rocks requires relatively dry, residual bulk rock compositions. Since most melt is lost along the high-T prograde to peak segment of the P-T path, only a small fraction of melt is generally retained in the residual post-peak assemblage. Reduced melt volumes with cooling limit length scales of diffusion to the extent that diffusion-controlled corona growth occurs. On the prograde path, the low melt (or melt-absent) volumes required for diffusion-controlled corona growth are only commonly realized in mafic igneous rocks, owing to their intrinsic anhydrous bulk composition, and in dry, residual pelitic compositions that have lost melt in an earlier metamorphic event. Experimental work characterizing rate-limiting reaction mechanisms and their petrogenetic signatures in increasingly complex, higher-variance systems has facilitated the refinement of chemical fractionation and partial equilibration diffusion models necessary to more fully understand corona development. Through the application of quantitative physical diffusion models of coronas coupled with phase equilibria modelling utilizing calculated chemical potential gradients, it is possible to model the evolution of a corona through P-T-X-t space by continuous, steady-state and/or sequential, episodic reaction mechanisms. Most coronas in granulites form through a combination of these endmember reaction mechanisms, each characterized by distinct textural and chemical potential signatures with very different petrogenetic implications. An understanding of the inherent petrogenetic limitations of a reaction mechanism model is critical if an appropriate interpretation of P-T evolution is to be inferred from a corona. Since corona modelling employing calculated chemical potential gradients assumes nothing about the sequence in which the layers form and is directly constrained by phase compositional variation within a layer, it allows far more nuanced and robust understanding of corona evolution and its implications for the path of a rock in P-T-X space.
Keywords: Chemical potential; Diffusion; Igneous rocks; Minerals; Phase equilibria; Reaction rates; Rocks; Bulk-rock composition; Chemical Fractionation; Chemical potential gradient; Comparative analysis; Compositional variation; Compositional zonation; High-grade metamorphic rocks; Rate-limiting reaction; Metamorphic rocks; Chemical composition; Comparative study